Development of “Willingness to Become School Administrator and Adjustment Scale” - Temel Çalık; Emel Tüzel (International Journal of Assessment Tools in Education)
The purpose of this study is to develop a likert-style reliable and valid scale in order to measure teachers’ level of willingness and adjustment to become school administrator. Before developing the scale, the literature had been carefully reviewed. The content validity was provided by making the corrections according to experts’ suggestions. 221 primary and secondary school teacher participated in the validity and reliability studies. The exploratory factor analyses revealed that the scale involves 28 items within four factors. The explained variance was calculated 60.075% and Cronbach Alpha coefficient is .9075 for the reliability.